(untitled) (Research, Society and Development, 2021)
Benign prostatic hyperplasia (BPH) is a urinary alteration associated with symptoms in the lower urinary tract, which can be voiding urgency, pollakiuria, voiding effort and bladder tenesmus. Meta-blockers, used in drug treatment in some cases of BPH, can inhibit the muscles responsible for iris dilation, leading to the development of alphab intraoperative iris syndrome (SIFI). Thus, the aim of the following review was to relate alpha 1 adrenergic receptor antagonists in the treatment of BPH with the development of SIFI. This is a systematic literature review that uses the platforms PubMed, sciELO and Google Scholar as a database for researching scientific articles, with a time frame between 2016 and 2021, in English. According to the search engine, 10 results were found, 10 articles in the PubMed and Google Scholar databases and 0 in the SciELO database. Therefore, according to the literature analyzed, the relationship between the use of alpha-1 adrenergic receptor antagonists, especially tamsulosin, for the treatment of BPH and the development of SIFI was found.